Chitin digestibility is dependent on feeding behaviors, which determine acidic chitinase mRNA levels in mammalian and poultry stomachs - Tabata, Eri; Kashimura, Akinori; Kikuchi, Azusa; Masuda, Hiromasa; Miyahara, Ryo; Hiruma, Yusuke; Wakita, Satoshi; Ohno, Misa; Sakaguchi, Masayoshi; Sugahara, Yasusato; Matoska, Vaclav; Bauer, Peter O; et al. (Scientific reports, 2018)
Chitin, a polymer of N-acetyl-D-glucosamine (GlcNAc), functions as a major structural component in chitin-containing organism including crustaceans, insects and fungi. Recently, we reported that acidic chitinase (Chia) is highly expressed in mouse, chicken and pig stomach tissues and that it can digest chitin in the respective gastrointestinal tracts (GIT). In this study, we focus on major livestock and domestic animals and show that the levels of Chia mRNA in their stomach tissues are governed by the feeding behavior. Chia mRNA levels were significantly lower in the bovine (herbivores) and dog (carnivores) stomach than those in mouse, pig and chicken (omnivores). Consistent with the mRNA levels, Chia protein was very low in bovine stomach. In addition, the chitinolytic activity of E. coli-expressed bovine and dog Chia enzymes were moderately but significantly lower compared with those of the omnivorous Chia enzymes. Recombinant bovine and dog Chia enzymes can degrade chitin substrates under the artificial GIT conditions. Furthermore, genomes of some herbivorous animals such as rabbit and guinea pig do not contain functional Chia genes. These results indicate that feeding behavior affects Chia expression levels as well as chitinolytic activity of the enzyme, and determines chitin digestibility in the particular animals.
Keywords: messenger RNA; psi; Guinea Pigs; Chitin; Gene Expression Regulation; Dogs; skot; stravovací zvyklosti; Stomach; kur domácí; morčata; regulace genové exprese; chitinasy; Chitinases; žaludek; Chickens; RNA, Messenger; zvířata; chitin; Cattle; Species Specificity; Feeding Behavior; druhová specificita; Animals